Physiological and social needs in decision making teacher of Yayasan Al Mumtaz Pontianak - Ahmad Husain; Irsyad Afif Pribadi; Farah Putri Arijani (Enrichment : Journal of Management, 2023)
To create an ideal school environment, it starts from how an educator conducts teaching in the classroom, especially in terms of techniques in making a good and loving communication space for students. Based on Abraham Maslow's theory, there are a variety of ideas that do fulfill the rules of psychological needs for humans including physiological needs and social needs. Which is where pshysiological is related to the needs that are identical to the bilogical needs of humans, food clothing shelter and welfare in their work environment, while social needs are basically social needs experienced by humans, the point here is how the social needs of educators can be met or not. This Research results that The magnitude of the influence is influenced by 62.5% of physiological needs and social needs and 37.6% of them are influenced by factors other than physiological needs and social needs. So it is very important for teachers to pay attention to their physiological and social needs before making decisions in the learning process.